Epidemiology of African Swine Fever in Piggeries in the Center, South and South-West of Cameroon - Victor Ngu Ngwa; Abdelrazak Abouna; André Pagnah Zoli; Anna-Rita Attili (Veterinary Sciences, 2020)
African Swine Fever (ASF) is enzootic in Cameroon. A cross-sectional study was conducted in the center, south and south-west regions of Cameroon in order to determine: the knowledge, skills and practices at risk of pig breeders; the prevalence of the disease in piggeries; the genome of the circulating virus. A total of 684 blood samples were collected in 209 farms for RT-PCR and ELISA analyses at the National Veterinary Laboratory (LANAVET) annex in Yaoundé. Prevalences of 15.2% (95CI: 12.5–17.9%) by ELISA, 23.8% (95CI: 20.6–27.0%) by RT-PCR, and 15.2% (95CI: 12.5–17.9%) by ELISA-PCR, were recorded. Of the farmers surveyed, 90% knew about the ASF and 55.3% have already experienced it. The 47.4% of them would not be able to recognize ASF if it occurred and, according to them, the risk of the disease introduction in farms would be 32% linked to the animal health personnel who work on farms. Molecular characterization revealed that only ASF genotype-I variable 19T-RSs is circulating. ASF is still hovering at a risky rate over the pig sector of Cameroon. The control of ASF needs an epidemiological surveillance, a better involvement of all stakeholders, sensitization of breeders and an effective State support for producers.